Plasma and Synovial Fluid TrxR Levels are Correlated With Disease Risk and Severity in Patients With Rheumatoid Arthritis. Issue 6 (February 2016) - Xie, Zhijun; Sun, Jing; Li, Haichang; Shao, Tiejuan; Wang, Dawei; Zheng, Qi; Wen, Chengping
Abstract : Abstract: This study was designed and performed to establish the relationship between plasma and synovial fluid (SF) levels of thioredoxin reductase (TrxR) and disease activity in Chinese patients with rheumatoid arthritis (RA). This study consisted of a total of 224 patients diagnosed with RA, 224 age and sex-matched healthy controls, and 156 patient controls. The disease activity of RA patients was calculated as diseases activity score that include 28-joint counts (DAS 28), which was divided into low-diseases activity (LDA) and high-diseases activity (HDA) groups. Increased plasma TrxR was detected in patients with RA than healthy controls ( P  < 0.0001). With an area under the curve (AUC) of 0.874, plasma TrxR showed a evidently greater discriminatory ability than C-reactive protein (CRP; AUC, 0.815), antistreptolysin-O (ASO; AUC, 0.631), rheumatoid factor (RF, AUC, 0.793), and erythrocyte sedimentation rate (ESR, AUC, 0.789) in diagnosing RA. RA patients with HDA had significantly elevated TrxR levels in plasma and SF than did those with LDA ( P  < 0.0001). With an AUC of 0.874, plasma TrxR levels as an indicator for screening of HDA showed a significantly greater discriminatory ability than CRP (AUC, 0.690), ASO (AUC, 0.597), RF (AUC, 0.657), and ESR (AUC, 0.603). Similarly, SF TrxR levels as an indicator for screening of HDA also showed a significantly greater discriminatory ability as compared with above biomarkers. TrxR levels in plasma and SF were positively correlated with the severity of RA. TrxR levels may therefore serve as a new biomarker in addition of the traditional biomarkers for assessing the risk and severity of RA. Further analysis of TrxR release machinery may give us a new understanding of pathogenesis of RA.